Porcine reproductive and respiratory syndrome prevalence and processing fluids use for diagnosis in United States breeding herds - Kikuti, Mariana; Vilalta, Carles; Sanhueza, Juan; Melini, Claudio Marcello; Corzo, Cesar A. (Frontiers in Veterinary Science, 2022)
Introduction Processing fluids have been recently adopted by the U.S. swine industry as a breeding herd PRRS monitoring tool due to their increased representativeness of animals within the herd. Here, we use the Morrison Swine Health Monitoring Project (MSHMP) database, representative of ~50% of the U.S. swine breeding herd, to describe processing fluids submissions for PRRS diagnosis and their relation to PRRS prevalence and time to stability over time between 2009 and 2020. Methods An ecological time series Poisson regression modeling the number of status 1 farms and weekly percentage of processing fluids submissions for PRRS diagnosis was done. Time to stability was calculated for sites that detected a PRRS outbreak within the study period and modeled through a proportional hazards mixed effect survival model using production system as a random-effect factor and epiweek as a panel variable. Results Processing fluids diagnosis submissions increased starting in 2017. The difference between each year's highest and lowest weekly prevalence averaged 10.9% between 2009 and 2017, whereas it averaged 5.0% in 2018–2020 period. Each year's lowest weekly prevalence ranged from 11.3 to 19.5% in 2009–2017 and from 22.4 to 29.2% in 2018–2020. We also detected an increasing proportion of breeding sites that did not reach stability within 1 year of reporting an outbreak (chi-square for trend p < 0.0001). The total time to stability was not associated with the region of the country in which the site was located, the site’s air filtration status, its PRRS status before the outbreak, or the different statuses a site achieved to be classified as stable, when accounting for the production system in the multivariate model. However, a higher proportion of system-wide processing fluids use was associated with increased time to stability. Discussion Altogether, the temporal concurrence of processing fluids used for PRRS virus monitoring suggests that the adoption of this sampling strategy may help explain the changes observed in PRRS status 1 prevalence since 2018, although further studies are still needed.